Safety issues of herbal weight loss dietary supplements: hepatotoxicity and adulteration - Zhivikj, Zoran; Petreska Ivanovska, Tanja; Karapandzova, Marija; Kulevanova, Svetlana; Kadifkova Panovska, Tatjana; Petrushevska-Tozi, Lidija (Archives of Pharmacy, 2024)
Herbal weight loss supplements are widely used in the management of obesity, but consistent data to support long-term weight loss efficacy and safety are missing. Besides, legal framework for food supplements is less restrictive than regulation of medications. The objective of this review is to give weight to the fact that many weight loss supplements contain herbal compounds with unknown mechanism of action, increasing the risk for adverse effects, even toxicity, especially in co-administration with prescribed drugs. Hepatotoxicity ranging from elevated transaminases and autoimmune-like hepatitis to acute liver failure appears to be underrecognized, but is not uncommonly encountered. Another and even more serious concern is adulteration of weight loss supplements by illegal addition of unauthorized substances or medications to provide quick effects and to increase sales. Here are some significant data regarding the possible hepatotoxicity of frequently used herbal extracts, as well as the health risks related to some common adulterants. Towards safer use of supplements, a comprehensive and critical discussion of current regulatory principles is essential to address the existing gap between the increased use of food supplements and the lack of knowledge about their benefits, providing better protection for consumers.